2018
DOI: 10.1098/rsfs.2018.0044
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film structural coloration from simple fused scales in moths

Abstract: One contribution of 11 to a theme issue 'Living light: optics, ecology and design principles of natural photonic structures'.The metallic coloration of insects often originates from diverse nanostructures ranging from simple thin films to complex three-dimensional photonic crystals. In Lepidoptera, structural coloration is widely present and seems to be abundant in extant species. However, even some basal moths exhibit metallic coloration. Here, we have investigated the origin of the vivid metallic colours of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
3
16
0
Order By: Relevance
“…To increase our understanding of the colour production mechanisms, we performed optical modelling using three-dimensional models of lamina-only, ridge-only and lamina + ridge models. We focused on thin-film (lamina thickness) and diffraction grating (ridges) effects as these have been shown to be important in previous studies of Micropterigidae (albeit by cross-ribs [2022]) and in the springtail species T. vulgaris [20]. Our results confirm the role of longitudinal ridges in colour production but also indicate that simultaneous thin-film effects are at play, the importance of which is species dependent.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…To increase our understanding of the colour production mechanisms, we performed optical modelling using three-dimensional models of lamina-only, ridge-only and lamina + ridge models. We focused on thin-film (lamina thickness) and diffraction grating (ridges) effects as these have been shown to be important in previous studies of Micropterigidae (albeit by cross-ribs [2022]) and in the springtail species T. vulgaris [20]. Our results confirm the role of longitudinal ridges in colour production but also indicate that simultaneous thin-film effects are at play, the importance of which is species dependent.…”
Section: Discussionsupporting
confidence: 67%
“…A study of both fossil and extant members of the Micropterigidae (Lepidoptera), which have a single lamina with longitudinal ridges and cross-ribs, revealed a remarkably conserved pattern of scale nanostructures [20,21], with the striking golden coloration resulting from a combination of a thin film (scale thickness) and a diffraction grating through cross-ribs and longitudinal ridges [21]. Kilchoer et al [22] found that the thickness of the melanin-pigmented scale (thin film) was critical to colour variation, while D'Alba et al [20] demonstrated that the nanoscale cross-ribs between the longitudinal ridges produced golden coloration through a diffraction grating (most likely in an interaction with scale lamina thin-film effects). This last study also investigated the colour of golden scales of the springtail (Collembola) Tomocerus vulgaris , whose scales are characterized by a single lamina and continuous, longitudinal ridges with clear valleys lacking cross-ribs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been linked to silver/gold iridescence in the skipper butterfly Carystoides escalantei (Ge et al, 2017). Outside of the butterfly/skipper lineage, it has been best characterized in the Micropterigidae Micropterix calthella (Kilchoer et al, 2019), where the fused lamina acts as a bronze/gold thin-film reflector whose specularity is enhanced by the diffractive scattering of the overlaying microribs (D'Alba et al, 2019). Other likely examples include the Noctuidae moths Diachrysia (Plusia) balluca and Trichoplusia orichalcea (Ghiradella, 1991;Brink et al, 1995).…”
Section: Broadband Microrib Gratingsmentioning
confidence: 99%
“…Probably the simplest strategy to generate color is via the interference of incident light in a single thin film. This can, for example, be observed in pigeon feathers ( Yoshioka et al., 2007 ), fly wings ( Stavenga, 2014 ), and the wing scales of Micropterix moths ( Kilchoer et al, 2019b ). In all these integumental structures, the minute control of the thin film thickness determines the animal's coloration.…”
Section: Introductionmentioning
confidence: 99%